2021
DOI: 10.3390/pediatric13010005
|View full text |Cite
|
Sign up to set email alerts
|

Autism, Therapy and COVID-19

Abstract: While numerous treatments for ASD are available, intervention based on the principles and procedures of Applied Behavior Analysis (ABA) has garnered substantial scientific support. In this study we evaluated the effects of the lockdown during the COVID-19 pandemic outbreak, followed by quarantine provisions and during the three months after the resumption of activities. The study was conducted on a group of children taking part on a ABA-based intervention funded by the Local Health Authority (ASL) of the provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
0
10
0
6
Order By: Relevance
“…The domain behavior was addressed in 22 articles, all of which described changes in behavior (Amorim et al, 2020 ; Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Jacques et al, 2022 ; Kawabe et al, 2020 ; Lugo-Marín et al, 2021 ; Mete Yesil et al, 2022 ; Morris et al, 2021 ; Mumbardó-Adam et al, 2021 ; Mutluer et al, 2020 ; Nuñez et al, 2021 ; Panjwani et al, 2021 ; Polónyiová et al, 2022 ; Rabbani et al, 2021 ; Sergi et al, 2021 ; Tokatly Latzer et al, 2021 ; Türkoğlu et al, 2020 , 2021 ; Vasa et al, 2021 ). Medium level of evidence was observed in eight papers (Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; Türkoğlu et al, 2021 ; Vasa et al, 2021 ) and the hypothesis of worsening behavior was confirmed by six articles, Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; and Türkoğlu et al, 2021 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The domain behavior was addressed in 22 articles, all of which described changes in behavior (Amorim et al, 2020 ; Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Jacques et al, 2022 ; Kawabe et al, 2020 ; Lugo-Marín et al, 2021 ; Mete Yesil et al, 2022 ; Morris et al, 2021 ; Mumbardó-Adam et al, 2021 ; Mutluer et al, 2020 ; Nuñez et al, 2021 ; Panjwani et al, 2021 ; Polónyiová et al, 2022 ; Rabbani et al, 2021 ; Sergi et al, 2021 ; Tokatly Latzer et al, 2021 ; Türkoğlu et al, 2020 , 2021 ; Vasa et al, 2021 ). Medium level of evidence was observed in eight papers (Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; Türkoğlu et al, 2021 ; Vasa et al, 2021 ) and the hypothesis of worsening behavior was confirmed by six articles, Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; and Türkoğlu et al, 2021 .…”
Section: Resultsmentioning
confidence: 99%
“…Medium level of evidence was observed in eight papers (Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; Türkoğlu et al, 2021 ; Vasa et al, 2021 ) and the hypothesis of worsening behavior was confirmed by six articles, Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; and Türkoğlu et al, 2021 . Most articles (n = 13) observed an resurgence of previous behavioral problems (Berard et al, 2021 ; Bhat, 2021 ; Hosokawa et al, 2021 ; Mete Yesil et al, 2022 ; Mutluer et al, 2020 ; Nuñez et al, 2021 ; Panjwani et al, 2021 ; Polónyiová et al, 2022 ; Sergi et al, 2021 ; Tokatly Latzer et al, 2021 ; Türkoğlu et al, 2020 , 2021 ; Vasa et al, 2021 ), while others (n = 5) observed the emergence of new behavioral issues (Corbett et al, 2021 ; Mete Yesil et al, 2022 ; Mumbardó-Adam et al, 2021 ; Mutluer et al, 2020 ; Vasa et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experience had shown that the lack of strong collaboration between the health sector, education, social services and nongovernmental organizations, resulted in a more ineffective management of complex emergencies and poor health outcomes for these children. The child's understanding of COVID-19, COVID-19 illness in the family, low family income, and depression and anxiety symptoms in the parent increase the risk for poor mental health during the pandemic [25].…”
Section: Discussionmentioning
confidence: 99%